Local cell therapy using CCL19-expressing allogeneic mesenchymal stem cells exerts robust antitumor effects by accumulating CD103+ IL-12-producing dendritic cells and priming CD8+ T cells without involving draining lymph nodes - Yuichi Iida; Mamoru Harada (Journal for ImmunoTherapy of Cancer)
Background Immune checkpoint blockade is a promising anticancer therapy, whereas the presence of T cells in tumor sites is indispensable for its therapeutic efficacy. To promote the infiltration of T cells and dendritic cells (DCs) into the tumor, we previously proposed a local cell therapy using chemokine (C-C motif) ligand 19 (CCL19)-expressing immortalized syngeneic immortalized mesenchymal stem cells (syn-iMSC/CCL19). However, the preparation of syngeneic/autologous MSC from individual hosts limits the clinical application of this cell therapy.Methods In this study, we further developed a new cell therapy using allogeneic iMSC/CCL19 (allo-iMSC/CCL19) using several tumor mice models.Results The allo-iMSC/CCL19 therapy exerted drastic antitumor effects, in which the host’s T cells were induced to respond to allogeneic MSC. In addition, the allo-iMSC/CCL19 therapy promoted the infiltration of CD103+ interleukin (IL)-12-producing DCs and priming of CD8+ T cells at tumor sites compared with that using syn-iMSC/CCL19. The antitumor effect of allo-iMSC/CCL19 therapy was not influenced by fingolimod, a sphingosine 1-phosphate receptor modulator, implying no involvement of draining lymph nodes in the priming of tumor-specific T cells.Conclusion These results suggest that allo-iMSC/CCL19 therapy exerts dramatic antitumor effects by promoting the infiltration of CD103+ IL-12-producing DCs and thereby priming tumor-specific CD8+ T cells at tumor sites. This local cell therapy could be a promising approach to anticancer therapy, particularly for overcoming dysfunction in the cancer-immunity cycle.